2019
DOI: 10.3390/su11195335
|View full text |Cite
|
Sign up to set email alerts
|

A Green Closed-Loop Supply Chain Coordination Mechanism Based on Third-Party Recycling

Abstract: Taking an environment-friendly green closed-loop supply chain as the research object, this work established a two-stage closed-loop supply chain game model. Considering the influence of the environmental protection input on the whole supply chain, there are different decisions among the participants in the supply chain, and the different choices will have impacts on the benefits of the whole supply chain when manufacturers select a closed-loop supply chain model of third-party recycling. Hence, this work compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
55
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 81 publications
(55 citation statements)
references
References 31 publications
(34 reference statements)
0
55
0
Order By: Relevance
“…en, the retailer reacts to determine the product's retail price P i . Finally, the retailer sells products to consumers to meet market demand [24][25][26]. All members are rational and pursue own benefit maximization.…”
Section: Definitions and Assumptionsmentioning
confidence: 99%
See 1 more Smart Citation
“…en, the retailer reacts to determine the product's retail price P i . Finally, the retailer sells products to consumers to meet market demand [24][25][26]. All members are rational and pursue own benefit maximization.…”
Section: Definitions and Assumptionsmentioning
confidence: 99%
“…en, we put equations (24) and (25) into equations (20) and 22, and we get the optimal utility of the manufacturer when manufacturers distribute the equity concern:…”
Section: Decentralized Decision-making When Manufacturersmentioning
confidence: 99%
“…Su Jiafu et al (2019) established a two-stage closed-loop supply chain game model. In terms of the influence of the environmental protection input on the whole supply chain, the different choices will have impacts on the benefits of the whole supply chain when manufacturers select a closed-loop supply chain model of third-party recycling [41]. Xu Lang et al (2018) compared the decisions and profits in the centralized and decentralized scenarios, where a contract through revenue and cost sharing was provided to achieve the supply chain coordination in the framework of Nash negotiation, and the coefficient of sharing was obtained to improve the performance [42].…”
Section: Remanufacturing Supply Chain With Recycling Approachesmentioning
confidence: 99%
“…Based on the analysis above, it can be concluded that the former research on vehicle routing problems with time windows (VRPTW) and PEP focused on the factors of traffic congestion, vehicle composition and vehicle load, etc., rather than multi-path vehicle routing problems [21][22][23]. Therefore, a multi-path mixed-integer mathematical programming model with a time window was established, which aimed to optimize fuel cost, driver cost, vehicle depreciation and time-window penalty cost and determine the exact solution using CPLEX in Java.…”
Section: Introductionmentioning
confidence: 99%